Preclinical study of simultaneous pharmacokinetic and pharmacodynamic herb-drug interactions between Yin-Chen-Hao-Tang and spironolactone - Tun-Pin Hsueh; Tung-Hu Tsai (BMC, 2020)
Abstract Background The prevalence and therapeutic effects of the use of herbal remedies for chronic liver diseases make the combined administration of herbal products with conventional treatment unable to be ignored. This study investigated the pharmacokinetic and pharmacodynamic herb-drug interactions between the herbal formula Yin-Chen-Hao-Tang (YCHT) and spironolactone. Methods A selective high-performance liquid chromatography (HPLC) method was developed and validated for the detection of spironolactone and its metabolite canrenone in rat urine. The interaction study was conducted by collecting urine samples after oral administration of spironolactone alone or in combination with YCHT for 5 days. Urine pharmacokinetic parameters and urinary sodium, potassium, volume, and weight were analyzed. Results The results revealed significant increases in the cumulative amount and the area under the rate curve (AURC) of the metabolite canrenone after pretreatment with the high dose of YCHT. The urine weight and volume were significantly reduced dose-dependently as a result of pretreatment with YCHT. The urinary sodium-to-potassium ratio, which indicates diuretic effects, was also reduced in the high-dose YCHT condition. Conclusions Herb-drug pharmacokinetic and pharmacodynamic interactions between YCHT and spironolactone were observed in the study. The herb-drug interaction that appeared with a single dose of spironolactone should be considered when patients are being treated with a continuous administration of this drug.